Flow estimation from the speedometry technique by images of large-scale particles applied in flow to a free surface (Gaceta Técnica, 2021)
The objective of this study is to estimate the flow from the speedometer technique for large-scale particle images in free surface flow. The work consisted in the recording of videos in three campaigns, then these were extracted and processed for the calculation of the average surface velocity and finally the estimation of the flow, using open source software RIVeR and PIVlab. Velocity profiles were obtained for different types of tracers and heights; the flows with foam tracers presented adequate velocity profiles, the flows with polystyrene tracers were adequate only at 2.00 m in height and without tracers they showed adequate profiles only at 1.50 m, the product of the average surface velocity, area and mean velocity coefficient gives flow rates for each case studied. In conclusion, liquid soap foam tracers had higher flow rates, due to the adequate definition of the velocity profile curve and the greater magnitudes of velocity vectors. Therefore, the LSPIV technique proved to be simple, adaptable and affordable to find flow rates and speed rates
Keywords: LSPIV technique; hydrological measurement; hydrodynamics